WDHD1 is over‐expressed in nasopharyngeal carcinoma and may control the expression of ITGAV. Issue 1 (28th November 2022) - Wu, Ji‐Yun; Niu, Yi‐Tong; Huang, Su‐Ning; Tan, Yu‐Min; Yang, Zhen‐Dong; Fang, Ye‐Ying; Jiang, Li; Zhang, Ting‐Ting; Zeng, Xiao‐Fen; Peng, Yun‐Xi; Mo, Miao; Lin, Cai‐Xing; et al.
Abstract : Nasopharyngeal carcinoma (NPC) is a highly metastatic and invasive malignant tumor that originates in the nasopharynx. The DNA‐binding protein WD repeat and HMG‐box DNA‐binding protein 1 (WDHD1) are highly expressed in a variety of tumours, but its expression and mechanism of action in NPC have not been reported to date. To investigate the involvement of WDHD1 in NPC, we first mined databases for the gene expression profile of NPC. Immunohistochemistry (IHC) was performed on 338 cases of NPC and 112 non‐NPC samples to verify the results. We report that the expression of WDHD1 is significantly elevated in NPC. ChIP‐seq was used to show that integrin alpha V (ITGAV) and WDHD1 exhibit a significant binding peak in the promoter region of the ITGAV gene. The expression levels of ITGAV and WDHD1 exhibit a significant positive correlation, and IHC was performed to show that ITGAV is highly expressed in NPC. Expression of ITGAV increased after overexpression of WDHD1, suggesting that ITGAV may be a potential target gene of WDHD1. Pathway analysis showed that both genes were closely related to the cell cycle, and flow cytometry was used to further confirm that decreased expression of WDHD1 significantly increased the number of apoptotic cells. In conclusion, our results suggest that expression of WDHD1 is increased in NPC and is likely to be associated with the NPC cell cycle; thus, we propose that WDHD1 may have the potential as a target gene for primary screening and treatment of NPC. Abstract : Comprehensive analysis showed that WDHD1 is highly expressed in nasopharyngeal carcinoma (NPC) tissues, and it may affect cell apoptosis by regulating the expression of ITGAV. Our data suggest that WDHD1 may play a role in the malignant progression of NPC.